The Influence of Consumer Motivation, Consumer Perceptions and Attitudes Towards Product Purchase Decisions at PT. Unikitz Bersatu Group Medan - Irvan Rolyesh Situmorang (Jurnal Manajemen Bisnis Eka Prasetya, 2023)
This study aims to determine the influence of consumer motivation, perception, and consumer attitudes on Product Purchase Decisions. The phenomenon that occurs in this study is the reduced purchase decision of products by consumers. The research methodology used is a quantitative descriptive method. The type of data used in this study is quantitative data. The research population that will be used in the study is all consumers who make purchases at the company in 2022, which is 12,139 consumers. Using the Slovin formula with an error rate of 5%, a total sample of 100 respondents was obtained. The data were analyzed using the multiple linear regression analysis method with the analysis results Y = 0.153 + 0.366 + 0.215 + 0.795 + e. The results of the research analysis show that Consumer Motivation has a positive and significant influence on Purchasing Decisions. The results of the analysis show that Quality Perception has a positive and significant influence on Purchasing Decisions. The results of the analysis show that consumer attitudes have a positive and significant influence on purchasing decisions. Simultaneously, the results showed that Consumer Motivation, Quality Perceptions and Consumer Attitudes have a positive and significant impact on Purchasing Decisions